Effects of invasive plant species on species diversity: implications on ruderal vegetation in Bratislava City, Slovakia, Central Europe - Alena Rendeková (Acta Societatis Botanicorum Poloniae, 2019)
Invasive species pose one of the most serious global environmental threats. Our study aimed to examine the correlation between the proportion of invasive alien taxa and species diversity of ruderal vegetation in the urban ecosystem of Bratislava, located in Central Europe. Ruderal habitats serve as the means of spread of invasive species to seminatural and natural habitats. Twenty-six invasive taxa were recorded among the ruderal vegetation of Bratislava. The majority of the recorded invasive species were neophytes, which came from North America and represent the Asteraceae family. Half of them were introduced accidentally, whereas the remaining species were introduced deliberately. Correlation and regression analyses showed that the proportion of invasive taxa has a negative effect on the species diversity of all the analyzed syntaxa in the ruderal vegetation of Bratislava.